1998
DOI: 10.1007/s004240050565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ruthenium red on membrane ionic currents in urinary bladder smooth muscle cells of the guinea-pig

Abstract: Three major ionic currents, Ca2+-dependent K+ current (IK-Ca), delayed rectifier type K+ current (Ikd) and Ca2+ current (ICa), were activated by depolarization under whole-cell clamp in single smooth muscle cells isolated from guinea-pig urinary bladder. Externally applied ruthenium red (RuR) reduced the amplitude of IK-Ca and ICa at 0 mV (IC50 values were 4.2 and 5.6 muM, respectively), but did not affect IKd. Spontaneous transient outward currents (STOCs) and caffeine-induced outward currents (Icaf) at -30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
(42 reference statements)
3
12
0
Order By: Relevance
“…Our study showed that hyperglycemia caused a significant increase in the bladder weight and a dramatic decrease in the bladder strip contraction (per 100 mg) caused by EFS, and coffee or caffeine treatment was able to significantly decrease the bladder weight and potentiate the strip contraction (per 100 mg) in the diabetic rat. These results indicate that such potentiated neurogenic bladder contraction may be attributable to the activation of Ca ] i ) is an essential process for many different cellular functions in a variety of cell types [16] . Two types of Ca 2+ release operate in the SR of smooth muscle cells: ryanodine-receptor mediated Ca 2+ release and inositol 1,4,5-trisphosphate-induced Ca 2+ release [16,17] .…”
Section: Discussionmentioning
confidence: 90%
“…Our study showed that hyperglycemia caused a significant increase in the bladder weight and a dramatic decrease in the bladder strip contraction (per 100 mg) caused by EFS, and coffee or caffeine treatment was able to significantly decrease the bladder weight and potentiate the strip contraction (per 100 mg) in the diabetic rat. These results indicate that such potentiated neurogenic bladder contraction may be attributable to the activation of Ca ] i ) is an essential process for many different cellular functions in a variety of cell types [16] . Two types of Ca 2+ release operate in the SR of smooth muscle cells: ryanodine-receptor mediated Ca 2+ release and inositol 1,4,5-trisphosphate-induced Ca 2+ release [16,17] .…”
Section: Discussionmentioning
confidence: 90%
“…It is likely that the latter effects were due to inhibition of cation and/or voltageoperated L-type Ca 2ϩ channels on smooth muscle cells (11,25,31). When the effects of these drugs were studied on firing evoked by von Frey hair compression of transduction sites, SKF 96365 still significantly inhibited mechanotransduction, suggesting an involvement of mechanogated channels (possibly belonging to the TRP family).…”
Section: Discussionmentioning
confidence: 92%
“…There may be additional, as yet unknown 2P channels present in cells (the genome of Caenorhabditis elegans contains more than 40 genes encoding 2P K ϩ channels), and although RR discriminates well between members of TASK currents, it also inhibits TRAAK, and additional 2P channels may also be affected. RR also affects the intermediate and large conductance Ca 2ϩ -activated K ϩ channels (37), the nonspecific cation channel vanilloid receptor (38), and other more distantly related ion transport mechanisms (39,40). The lack of specific inhibitors and/or antibodies against the various forms of TASK channels and their close relatives, together with their low single channel conductance and mean open times (in the range of 1 ms (41)) makes discrimination between TASK channels by high resolution electrophysiological studies extremely difficult.…”
Section: Discussionmentioning
confidence: 99%